Pelatihan Algoritma Pemrograman Untuk Persiapan OSN Informatika Siswa SMA Kolose de Britto Yogyakarta - Jong Jek Siang; Lucia Dwi Krisnawati; Yuan Lukito; Lukas Chrisantyo; Raden Gunawan Santoso (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
The Olimpiade Sains Nasional (OSN) in Informatics is a prestigious competition that demands mastery of programming and problem-solving. SMA Kolese de Britto, located in Yogyakarta, faced a challenge in preparing its students for this event due to a limited number of qualified teachers. To address this problem, a community service program in the form of intensive training was implemented through a collaboration with the Fakultas Teknologi Informasi (FTI) UKDW. The program's execution involved five key stages: partner application, coordination and planning, material preparation, training implementation, and evaluation. The training was conducted in 12 sessions, both online and offline, for five students who were pre-selected by the school. The material focused on algorithms, logic, and C++ programming, all highly relevant to past OSN questions. The results showed that one student successfully advanced to the provincial level of the Olimpiade Sains Nasional. Evaluations from both the school and the participating students revealed very high satisfaction, with an average score of 4.5 to 5 on a 5-point scale. This outcome underscores the training's relevance and effectiveness. The students' initial lack of programming knowledge was also successfully overcome. Both the school and the students highly recommend that a similar training program be held again in the following year.